Predictors of Transplant Regret: A Case–Control Study Nested Within a Prospective Cohort of HSCT Recipients - Janae L. Kirsch; James R. Cerhan; William J. Hogan; Holly C. Edwards; Christi A. Patten; Tabetha Brockman; Christine Hughes; Angela Dispenzieri; Stephen M. Ansell; Dennis A. Gastineau; Shawna L. Ehlers (Cancer Medicine)
ABSTRACT Objective To explore pre–hematopoietic stem cell transplant (HSCT) demographic, disease, and psychological factors predictive of future transplant regret and to determine post‐HSCT variables associated with regret. Patients and Methods HSCT candidates participated in a prospective cohort study (June 2008–October 2013) examining health behaviors and HSCT outcomes, including completion of standardized surveys at pre‐HSCT (baseline) and 1‐year post‐HSCT. Cases were participants that endorsed regret at 1‐year post‐HSCT follow‐up, and controls were participants without regret at 1 year, matched on age, sex, and transplant type. For cases and controls, pre‐HSCT psychosocial evaluations were abstracted from the electronic health record and coded to determine the Psychosocial Assessment of Candidates for Transplantation score, psychosocial stressors, and mental health diagnoses. The association of selected factors with regret was estimated with odds ratios and 95% confidence intervals from conditional logistic regression models. Results At post‐HSCT, 49 participants of 638 endorsed transplant regret (8%) and formed the case group; 98 controls were matched from remaining participants. Cases and controls were well matched on age (56.6 vs. 57.2 years), sex (both groups 34.7% female), and transplant type (both groups 81.6% autologous). After controlling for the number of hospitalizations and active treatment status, conditional logistic regression revealed that patients who endorsed regret were 3.7 times (95% CI = 1.37–9.69, p = 0.008) more likely to not be in remission compared to controls at 1‐year post‐HSCT. Conclusion Matched case–control analyses revealed that no pre‐HSCT variables collected during the pre‐HSCT evaluation period were predictive of transplant regret, while poorer outcomes at 1‐year after transplant were associated with regret.